Ripple‐related firing of identified deep CA1 pyramidal cells in chronic temporal lobe epilepsy in mice. Issue 2 (4th March 2019) - Marchionni, Ivan; Oberoi, Michelle; Soltesz, Ivan; Alexander, Allyson
Summary: Objective: Temporal lobe epilepsy (TLE) is often associated with memory deficits. Reactivation of memory traces in the hippocampus occurs during sharp‐wave ripples (SWRs; 140‐250 Hz). To better understand the mechanisms underlying high‐frequency oscillations and cognitive comorbidities in epilepsy, we evaluated how rigorously identified deep CA1 pyramidal cells (dPCs) discharge during SWRs in control and TLE mice. Methods: We used the unilateral intraamygdala kainate model of TLE in video–electroencephalography (EEG) verified chronically epileptic adult mice. Local field potential and single‐cell recordings were performed using juxtacellular recordings from awake control and TLE mice resting on a spherical treadmill, followed by post hoc identification of the recorded cells. Results: Hippocampal SWRs in TLE mice occurred with increased intraripple frequency compared to control mice. The frequency of SWR events was decreased, whereas the overall frequency of SWRs, interictal epileptiform discharges, and high‐frequency ripples (250‐500 Hz) together was not altered. CA1 dPCs in TLE mice showed significantly increased firing during ripples as well as between the ripple events. The strength of ripple modulation of dPC discharges increased in TLE without alteration of the preferred phase of firing during the ripple waves. Significance: These juxtacellular electrophysiology data obtained from identified CA1 dPCs from chronically epileptic mice are in general agreement with recent findings indicating distortion of normal firing patterns during offline SWRs as a mechanism underlying deficits in memory consolidation in epilepsy. Because the primary seizure focus in our experiments was in the amygdala and we recorded from the CA1 region, these results are also in agreement with the presence of altered high‐frequency oscillations in areas of secondary seizure spread.